The Mitrokhin archive : the KGB in Europe and the West - Andrew, Christopher; Mitrokhin, Vasili (London : Penguin, 1999)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: geheime diensten; spionage; Sovjet-Unie.